PENGEMBANGAN MEDIA PUZZLE DALAM PEMBELAJARAN CARA MEMBACA LAMBANG SIMBUL/GAMBAR DENGAN METODE KNOW WANT LEARNED GUNA MENINGKATKANeKEMAMPUAN MEMBACA PEMAHAMAN - Sugeng Santosa; Nunuk Suryani; Juhana Juhana (Widya Wacana: Jurnal Ilmiah, 2022)
This study aims to (1) develop puzzle media in learning how to read symbols/images with the Know Want Learned method to improve reading comprehension skills in fourth grade students, (2) describe the quality and feasibility of learning media products in the form of puzzles using the know want learned method. in improving the reading comprehension ability of fourth grade students. This study uses research and development procedures (Research and Development). The media puzzle development procedure consists of five stages, namely: analysis, design, development, implementation, and evaluation. Product trials are carried out on a small and large scale. The population is 10 elementary schools in Cluster I Ki Hajar Dewantoro, Ngargoyoso district, sample 3 public elementary schools. Data collection techniques using tests, observations, journals, and questionnaires. The data analysis technique is in the form of data analysis of puzzle media products, prerequisite test, and discriminatory test. The results showed that the puzzle learning media that the researcher developed referred to the needs of students and teachers needs, with the aim of improving students reading comprehension skills. The puzzle media that the researcher developed is an educational learning media in the form of a rectangle with a size of 20 cm x 30 cm made of staff so that it is safe for students to use as learning media. The puzzle media that the researcher developed included symbol puzzles, symbol puzzles, and symbol/image puzzles. This Puzzle Learning Media is effectively used in learning how to read symbols/pictures because it can improve reading comprehension skills for fourth grade elementary school students in Cluster I Ki Hajar Dewantoro. Keywords: development, puzzle, ability to read symbols.